MATA DALAM BAHASA - Acep Iwan Saidi (Fakultas Seni Rupa dan Desain ITB, 2006)
A body is a language, every inch of our corpse, says something. Why, for instance, our fingers' sizes are not similar? Certainly there is a meaning, a verbal-message. Likewise for the eyes, in visual-culture eyes are center-of-sensors to a human body. With linguistic perpective in this essay, it is detailed the utmost-impotant function of eyes.